Пролегомены к политической социологии ленинизма - Кутуев, П. (Социология: теория, методы, маркетинг, 2000)
Drawing heavily upon Weber’s value-free political sociology and Ken Jowitt’s vision of Leninism, the paper suggests that Leninist regimes are best conceptualized as a unique blend of charismatic, impersonal and traditional elements. Being a political and ideological response to conditions of national dependency in peripheral societies of traditional bent, Leninism created new political entity — the party as organizational weapon — which was a bearer of impersonal charisma. Application of analitical tool box elaborated by Weber and Jowitt increases our understanding of the internal developmental logic of Leninist regimes while helping to draw a distinction between revolutionary system-building politics of Leninist type and nationalist modernizing regimes of the Third World on the one hand and fascist regimes on the other. The article offers an account of developmental stages of Leninist regimes— trans - formation, consolidation, and inclusion. The latter stage purpose was to accommodate new, more complex social and cultural environment to regime’s demands. Having lost its combat task during inclusion stage, the party entered the period of neotraditionalist routinization of its organizational charisma which resulted in a clash between Leninist status oriented cadres and emergent civic oriented styles of life. Regime’s inability to resolve the tension between the two mutually exclusive elements — party cadre and citizen — resulted in “Leninist extinction” and disappearance of Leninism as an alternative life style.